Student Response to the Implementation of E-Module-Assisted Cybergogy in Junior High School Students - Ramadhani, Novitasari; Subekti, Hasan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The low involvement of students in learning is still a challenge, one of which is influenced by the lecture method, which is still dominant in the teaching and learning process. The application of technology-based learning, such as e-module-assisted cybergoth, is expected to increase students' positive responses. This study aims to analyze students' responses to the application of e-module-assisted cybergogy in science learning. This study uses a quasi-experimental method with a one-shot case study design involving 32-grade VIII-D SMPN 1 Bagor students. Data was collected through student response questionnaires and analyzed using descriptive statistics. The results showed that implementing e-module-assisted cybergogy resulted in very positive student responses, with an average response score of 99.1%. In conclusion, this approach can increase student engagement in science learning. This research implies that educators can adopt e-module-assisted cybergogy to create more interactive and innovative learning.